Analisa Pengaruh Unsur Terhadap Kekerasan High Manganese Steel Menggunakan Metode Regresi Linier Berganda - Ervita Rahma Budiyarti; Budianto Budianto; Nurvita Arumsari (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
Apie Indo Karunia is one of the companies engaged in foundry located in Sidoarjo. Thiscompany is a company that works based on orders / orders from consumers (Make to Order).Products are made of metal casting processes, one of which is High Manganese Steel which has highmanganese content. Each metal has a different level of hardness, depending on the type of metal itself.There are several factors that can affect the value of metal products. This content in the metal canproduce a level of violence. Multiple Linear Regression Method to fix this problem. The first step is toinput data, then determine what factors are mostly affectMultiple Regression. From the result ofanalyze we can know that carbon and posphor are have big impact to high manganese steel’shardness